PENDIDIKAN MORAL: SEBUAH DUNIA JUNGKIR BALIK - Haricahyono, Cheppy (Jurnal Bestari, 1992)
God createdmen to be the leaders of the universe. He gave them a special equipment that was nor owned by other creatures. Everyman has a intellectual and brain which they can distinguish themselves from animals. They will lead the world when they can maximisate their intellectual capacty. It is, however, must be based on moral consideration. The life long education will be meaningless without existing morality as the fundamental aspect of their life.